Pembrolizumab plus pemetrexed‐platinum for metastatic nonsquamous non–small‐cell lung cancer: KEYNOTE‐189 Japan Study. Issue 8 (15th June 2021) - Horinouchi, Hidehito; Nogami, Naoyuki; Saka, Hideo; Nishio, Makoto; Tokito, Takaaki; Takahashi, Toshiaki; Kasahara, Kazuo; Hattori, Yoshihiro; Ichihara, Eiki; Adachi, Noriaki; Noguchi, Kazuo; Souza, Fabricio; et al.
Abstract: Pembrolizumab plus pemetrexed‐platinum significantly improved overall survival (OS) and progression‐free survival (PFS) with manageable safety compared with placebo plus pemetrexed‐platinum in patients with previously untreated metastatic nonsquamous non–small‐cell lung cancer (NSCLC) without EGFR/ALK alterations in the global, randomized, double‐blind, phase 3 KEYNOTE‐189 study. We present results of Japanese patients enrolled in the KEYNOTE‐189 global and Japan extension studies. Patients were randomized 2:1 to intravenous pembrolizumab 200 mg or placebo every 3 weeks (Q3W) for up to 35 cycles. All patients received pemetrexed 500 mg/m 2 plus the investigator's choice of cisplatin or carboplatin Q3W for four cycles, followed by maintenance pemetrexed 500 mg/m 2 Q3W (all intravenous). Co–primary endpoints were OS and PFS. Forty Japanese patients enrolled (pembrolizumab, n = 25; placebo, n = 15). At data cutoff (20 May 2019; median time from randomization to data cutoff, 18.5 [range, 14.7‒38.2] months), the median OS was not reached in the pembrolizumab plus pemetrexed‐platinum arm; the median OS was 25.9 (95% confidence interval [CI], 11.9‒29.0) months in the placebo plus pemetrexed‐platinum arm (hazard ratio [HR] .29; 95% CI, .07‒1.15). The median (95% CI) PFS was 16.5 (8.8‒21.1) compared with 7.1 (4.7‒21.4) months (HR, .62; 95% CI, .27‒1.42), respectively. There were no grade 5 adverse events (AE). Grade 3/4 AE occurred in 72% vs 60% of patients in the pembrolizumab vs placebo arms; 40% vs 20% had immune‐mediated AE, and 4% vs 0% had infusion reactions. Efficacy and safety outcomes were similar to those from the global study and support first‐line therapy with pembrolizumab plus pemetrexed‐platinum in Japanese patients with nonsquamous NSCLC without EGFR / ALK alterations. Abstract : In conclusion, consistent with the global KEYNOTE‐189 study, pembrolizumab in combination with pemetrexed and platinum improved OS, PFS, ORR, and PFS2 compared with placebo plus pemetrexed‐platinum and demonstrated a manageable safety profile in Japanese patients with previously untreated metastatic nonsquamous NSCLC. The results from this study confirm the role of pembrolizumab plus pemetrexed‐platinum as a first‐line standard‐of‐care therapy for Japanese patients with metastatic nonsquamous NSCLC.